Brachytherapy and radical prostatectomy in patients with early prostate cancer - Ferreira,Adriana Souza Sérgio (2015)
Summary Objective: this study analyzes the survival of prostate cancer patients cared for at a hospital in Minas Gerais, Brazil according to one of the following treatments: iodine-125 seed implantation or radical prostatectomy. From January 2002 to December 2005, 129 patients underwent either brachytherapy (64 patients) or surgery (65 patients). Methods: all had prostate-specific antigen, Gleason scores and clinical stage recorded prior to treatment. Biochemical relapse was defined as prostate-specific antigen (PSA)>0.4ng/mL for radical prostatectomy, and any elevation equal or higher than 2ng/mL over the PSA nadir for implanted patients. To analyze the effect of treatment on biochemical recurrence-free survival (BRFS), Kaplan-Meier curves and Cox regression were generated. Mean follow-up time was 56.1 months for patients with the implant, and 26.6 months for those operated on. BRFS in 5 years was 69% (95% CI: 58.18-77.45) for the whole cohort. Discussion: when stratified according to treatment, survival of patients who had undergone brachytherapy (79.70%) was higher to those operated on (44.30%; pvalue= 0.0056). Upon multivariate analysis, independent predictors were iPSA (HR: 2.91, 95% CI: 1,32-6,42), Gleason score (HR: 2.18, 95% CI: 1,00-4,81) and treatment modality (HR: 2.61, 95% CI: 1.18-5,75). Risk of biochemical failure was higher with surgery than brachytherapy, which may be related to the failure criteria adopted, which is different for each therapy, as well as the high rate of histological progression between preoperative prostate biopsy and surgical specimen. Conclusion: it was found that brachytherapy is a good therapeutic option for low risk prostate cancer.